2001
DOI: 10.1037/0012-1649.37.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Body-image and eating disturbances prospectively predict increases in depressive symptoms in adolescent girls: A growth curve analysis.

Abstract: Using data from a longitudinal community study (N = 231), the authors tested whether body-image and eating disturbances might partially explain the increase in depression observed in adolescent girls. Initial pressure to be thin, thin-ideal internalization, body dissatisfaction, dieting, and bulimic symptoms, but not body mass, predicted subsequent increases in depressive symptoms, as did increases in these risk factors over the study. There was also prospective support for each of the hypothesized mediational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
424
10
24

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 558 publications
(494 citation statements)
references
References 58 publications
(98 reference statements)
36
424
10
24
Order By: Relevance
“…For instance, a causal relationship to cannabis use for boys could not be delineated, and no strong evidence for such a relationship is found in the scientific literature (Moore et al, 2007). As for eating problems, while some prospective research indicates a causal effect of eating pathology on depressive symptoms (Marmorstein et al, 2008;Stice & Bearman, 2001), other studies reveal prospective reciprocal effects of these two variables (Presnell, Stice, Seidel, & Madeley, 2009), indicating a partial reverse causal relationship. As such, the current knowledge of risk factors for such symptoms does not provide the possibility to draw strong conclusions about factors that causally explain such changes.…”
Section: Secular Trends In Depressive Symptoms 24mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a causal relationship to cannabis use for boys could not be delineated, and no strong evidence for such a relationship is found in the scientific literature (Moore et al, 2007). As for eating problems, while some prospective research indicates a causal effect of eating pathology on depressive symptoms (Marmorstein et al, 2008;Stice & Bearman, 2001), other studies reveal prospective reciprocal effects of these two variables (Presnell, Stice, Seidel, & Madeley, 2009), indicating a partial reverse causal relationship. As such, the current knowledge of risk factors for such symptoms does not provide the possibility to draw strong conclusions about factors that causally explain such changes.…”
Section: Secular Trends In Depressive Symptoms 24mentioning
confidence: 99%
“…Longitudinal studies among adolescents and young adults show several variables to be prospectively related to depressive symptoms. These include a variety of psychological problems, including disordered eating (Marmorstein, von Ranson, Iacono, & Malone, 2008;Stice & Bearman, 2001), conduct problems (Nock, Kazdin, Hiripi, & Kessler, Secular trends in depressive symptoms 6 2006), and substance abuse (Marmorstein, Iacono, & Malone, 2010). Moreover, studies have indicated that variables related to appearance, such as appearance dissatisfaction and body mass index (BMI), may be risk factors for depressive symptoms (Bearman & Stice, 2008;Needham & Crosnoe, 2005;Paxton, Neumark-Sztainer, Hannan, & Eisenberg, 2006).…”
mentioning
confidence: 99%
“…Perceived pressure to be thin has also been found to predict subsequent increases in negative affect (Stice & Bearman, 2001). Finally, perceived pressure to be thin predicted increases in dieting and eating pathology (Byely et al, 2000;Field, Camargo, Taylor, Berkey, & Colditz, 1999;Field et al, 2001;Stice, 2001;Wertheim, Koerner, & Paxton, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…These same pernicious messages are thought to foster negative affect, because appearance is a central evaluative dimension for women in Western culture (Stice & Bearman, 2001). The body dissatisfaction and negative affect that putatively result from pressure to be thin may, in turn, increase the subsequent risk for the emergence of restrictive dieting and eating pathology (Paxton et al, 1999;McCarthy, 1990;Stice, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In cross-sectional and prospective studies of adolescents and young adults, BDS is predictive of low self-esteem (6,7) , depressive symptoms (3,(7)(8)(9)(10) , sleep disturbance, stress and low confidence in social situations, often irrespective of actual weight status (4,11) .…”
mentioning
confidence: 99%